Pengaruh Koneksi Politik, Direksi Luar Perusahaan, Komisaris Independen dan Gender Direksi terhadap Kinerja Bank Pembangunan Daerah: Inovasi Keuangan sebagai Variabel Moderasi - Mardiana Azizah; Efa Yonnedi (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This research is intended to examine the influence of political connections, outside directors, independent commissioners and gender of directors on the performance of regional development banks with financial innovation as a moderating variable. The object in this study is the 2017-2021 Regional Development Bank (BPD). The total sample in this study was 26 BPD. The analytical method used in this research is to carry out Partial Least Square (PLS) analysis assisted by the SmartPLS 3.0 program. The findings show that political connections have no effect on BPD performance, outside directors have a negative and significant effect on BPD performance, independent commissioners have no effect on BPD performance, directors' gender has a positive and significant effect on BPD performance, financial innovation does not moderate the influence of political connections on BPD performance, financial innovation moderates the influence of outside directors on BPD performance, financial innovation moderates the influence of independent commissioners on BPD performance, and financial innovation does not moderate the influence of directors' gender on BPD performance. It is hoped that the results of this research can contribute to academics in adding to the literature regarding the financial performance of Regional Development Banks (BPD) and also increase insight for companies in improving financial performance.